2024
DOI: 10.1111/eva.13654
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics, life‐history tactics, and mixed‐stock subsistence fisheries in the northernmost American Atlantic salmon populations

Alexandre Carbonneau,
Julien April,
Eric Normandeau
et al.

Abstract: While Atlantic salmon (Salmo salar) of the northernmost American populations is alimentary, economically, and culturally important for Ungava Inuit communities (Nunavik, Canada) and might play a key role in the persistence of the species in a global warming context, many mysteries remain about those remote and atypical populations. Thus, our first aim was to document the genomic structure of the Nunavik populations. The second objective was to determine whether salmon only migrating to the estuary without reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Two studies investigated the effects of hatchery programs on diversity (McPhee et al, 2024) and fitness (Dayan et al, 2024) of natural populations, while multiple studies examined effects to diversity of altered habitats (Hugentobler et al, 2024;Moccetti et al, 2024) or harvest impacts (Miettinen et al, 2024). Two studies characterized variation at the genomic (Carbonneau et al, 2024) or transcriptomic (Kokkonen et al, 2024) level to assist with conservation of rare taxa and remote populations, while Thompson et al (2024) Parentage analyses of returning adults indicated that the program provided a demographic boost in productivity in the 3 years evaluated (ranging from 6.0-48.6 times higher productivity), presumably due to limited spawning habitat and density dependence during incubation stages for fish in natural habitat. There was no statistical difference in adult run timing or size at age between hatchery reared versus wild fish, but hatchery-reared fish were younger as returning adults on average than wild fish.…”
Section: Conservation Of Life History Variation and Genetic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies investigated the effects of hatchery programs on diversity (McPhee et al, 2024) and fitness (Dayan et al, 2024) of natural populations, while multiple studies examined effects to diversity of altered habitats (Hugentobler et al, 2024;Moccetti et al, 2024) or harvest impacts (Miettinen et al, 2024). Two studies characterized variation at the genomic (Carbonneau et al, 2024) or transcriptomic (Kokkonen et al, 2024) level to assist with conservation of rare taxa and remote populations, while Thompson et al (2024) Parentage analyses of returning adults indicated that the program provided a demographic boost in productivity in the 3 years evaluated (ranging from 6.0-48.6 times higher productivity), presumably due to limited spawning habitat and density dependence during incubation stages for fish in natural habitat. There was no statistical difference in adult run timing or size at age between hatchery reared versus wild fish, but hatchery-reared fish were younger as returning adults on average than wild fish.…”
Section: Conservation Of Life History Variation and Genetic Diversitymentioning
confidence: 99%
“…Two studies investigated the effects of hatchery programs on diversity (McPhee et al., 2024 ) and fitness (Dayan et al., 2024 ) of natural populations, while multiple studies examined effects to diversity of altered habitats (Hugentobler et al., 2024 ; Moccetti et al., 2024 ) or harvest impacts (Miettinen et al., 2024 ). Two studies characterized variation at the genomic (Carbonneau et al., 2024 ) or transcriptomic (Kokkonen et al., 2024 ) level to assist with conservation of rare taxa and remote populations, while Thompson et al. ( 2024 ) used genomic study to better understand life history diversity of imperiled populations.…”
Section: Synopsis Of Articles—advances In Salmonid Geneticsmentioning
confidence: 99%
See 1 more Smart Citation